2003
DOI: 10.1002/acp.878
|View full text |Cite
|
Sign up to set email alerts
|

Improving calibration without training: the role of task information

Abstract: Medical students estimated probabilities that medical school applicants selected randomly from a defined population would be offered a place on the basis of information about eight characteristics of each one. Estimates were biased in favour of acceptance and this was unaffected by mere provision of base rate information. However, a first experiment showed that provision of this information reduced miscalibration after each candidate had been discussed within small groups of participants. A second experiment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Instead, as recently argued by Rakow, Harvey, and Finer (2003), base rates must be presented in a manner that will effectively induce participants to consider them. Therefore, instead of providing one overall base rate to our participants, we provided the base rate (of successful tosses) for each of the 10 different toss locations that comprised our task.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, as recently argued by Rakow, Harvey, and Finer (2003), base rates must be presented in a manner that will effectively induce participants to consider them. Therefore, instead of providing one overall base rate to our participants, we provided the base rate (of successful tosses) for each of the 10 different toss locations that comprised our task.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we thought that by highlighting those trials in which the equation and decision maker disagreed on the first block of trials, we would thereby be concentrating on those instances in which improvement in calibration would have a very large potential benefit. Rakow, Harvey, and Finer (2003) provided medical students with important base-rate information to help them decide which of a sample of 36 medical school applicants were and were not admitted. The authors found that some medical students did not think that the base rate of acceptance of this sample was representative of the population, and other medical students simply did not take sufficient account of whatever base rate they thought was accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indeed demonstrated the positive effect of feedback on reduction in overconfidence in some cases [48,49]. However this effect is susceptible to various factors, such as task difficulty [50], estimation order (i.e., first estimation vs. following estimations, see Baranski and Petrusic [ 51 ], Lichtenstein and Fischhoff [52]), and type of judgment (i.e., high probability vs. low probability, see Baranski and Petrusic [51]).…”
Section: Debiasing Techniquesmentioning
confidence: 98%